Clinical and social factors associated with increased risk for involuntary psychiatric hospitalisation: a systematic review, meta-analysis, and narrative synthesis. (December 2019) - Walker, Susan; Mackay, Euan; Barnett, Phoebe; Sheridan Rains, Luke; Leverton, Monica; Dalton-Locke, Christian; Trevillion, Kylee; Lloyd-Evans, Brynmor; Johnson, Sonia
Summary: Background: Use of involuntary psychiatric hospitalisation varies widely within and between countries. The factors that place individuals and populations at increased risk of involuntary hospitalisation are unclear, and evidence is needed to understand these disparities and inform development of interventions to reduce involuntary hospitalisation. We did a systematic review, meta-analysis, and narrative synthesis to investigate risk factors at the patient, service, and area level associated with involuntary psychiatric hospitalisation of adults. Methods: We searched MEDLINE, PsycINFO, Embase, and the Cochrane Controlled Clinical Register of Trials from Jan 1, 1983, to Aug 14, 2019, for studies comparing the characteristics of voluntary and involuntary psychiatric inpatients, and studies investigating the characteristics of involuntarily hospitalised individuals in general population samples. We synthesised results using random effects meta-analysis and narrative synthesis. Our review follows Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and is registered on PROSPERO, CRD42018095103. Findings: 77 studies were included from 22 countries. Involuntary rather than voluntary hospitalisation was associated with male gender (odds ratio 1·23, 95% CI 1·14–1·32; p<0·0001), single marital status (1·47, 1·18–1·83; p<0·0001), unemployment (1·43, 1·07–1·90; p=0·020), receiving welfare benefits (1·71, 1·28–2·27; p<0·0001), being diagnosed with a psychotic disorder (2·18, 1·95–2·44; p<0·0001) or bipolar disorder (1·48, 1·24–1·76; p<0·0001), and previous involuntary hospitalisation (2·17, 1·62–2·91; p<0·0001). Using narrative synthesis, we found associations between involuntary psychiatric hospitalisation and perceived risk to others, positive symptoms of psychosis, reduced insight into illness, reduced adherence to treatment before hospitalisation, and police involvement in admission. On a population level, some evidence was noted of a positive dose-response relation between area deprivation and involuntary hospitalisation. Interpretation: Previous involuntary hospitalisation and diagnosis of a psychotic disorder were factors associated with the greatest risk of involuntary psychiatric hospitalisation. People with these risk factors represent an important target group for preventive interventions, such as crisis planning. Economic deprivation on an individual level and at the population level was associated with increased risk for involuntary hospitalisation. Mechanisms underpinning the risk factors could not be identified using the available evidence. Further research is therefore needed with an integrative approach, which examines clinical, social, and structural factors, alongside qualitative research into clinical decision-making processes and patients' experiences of the detention process. Funding: Commissioned by the Department of Health and funded by the National Institute of Health Research (NIHR) via the NIHR Mental Health Policy Research Unit.